2000
DOI: 10.2527/2000.78123001x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of injection position and transponder size on the performances of passive injectable transponders used for the electronic identification of cattle.

Abstract: A total of 686 Tiris half-duplex passive injectable transponders (PIT) of two sizes (23 and 32 mm) were randomly injected s.c. in three positions, armpit, ear scutulum, and upper lip, in 343 fattening calves (1 to 3 mo old). Injections were performed by two trained and two untrained operators. Losses and breakages on the farm were recorded at wk 1, 3, 7, 11, and 15 in restrained animals using two types of hand-held transceivers with a stick antenna. Dynamic reading efficiency (DRE) in animals running through a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
30
4
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 0 publications
9
30
4
1
Order By: Relevance
“…These findings agree with those of Conill et al (2000Conill et al ( , 2002 and Caja et al (2005), who found no negative effects in cattle, lambs and pigs in similar experiments. Only 1 piglet died (perineal injection group) in our experiment, but the necropsy confirmed that the cause of death was not related to transponder injection.…”
Section: Resultssupporting
confidence: 95%
“…These findings agree with those of Conill et al (2000Conill et al ( , 2002 and Caja et al (2005), who found no negative effects in cattle, lambs and pigs in similar experiments. Only 1 piglet died (perineal injection group) in our experiment, but the necropsy confirmed that the cause of death was not related to transponder injection.…”
Section: Resultssupporting
confidence: 95%
“…No differences between glass-and polymerencapsulated microchips were detected by Løken et al (2011). The use of longer glass-encapsulated transponders (23 or 32 by 3.8 mm) in suitable body sites (ear scutulum and armpit) of fattening calves slaughtered at 8 to 12 mo by Conill et al (2000) showed 93.0 to 98.5% readability, which differed according to body site and transponder size. When comparing our results of microchip readability of the long term (7 yr) in camels with short and mid term (0.5 to 2.1 yr) in horses and cattle, it is clear that the values of estimated yearly losses by using the Seroussi et al (2011) expression in our camels (5.1%; Table 2) were consistent and within the range of those previously calculated in horses (0 to 13.7%) and cattle (1.8 to 8.4%).…”
Section: Previously Applied Identificationmentioning
confidence: 87%
“…The World Small Animal Veterinary Association (2016) strongly recommended that any microchipped food-producing animal should carry an external ID to indicate that a microchip is present (i.e., to be recognized and recovered at slaughter) and in some cases their use may not be permitted. Conill et al (2000) reported recovery times of approximately 1 min at the slaughterhouse when 23 and 32 mm transponders were injected in the ear base and armpit of fattening calves. The smaller size of RFID microchips used in camels (i.e., 12 to 15 mm, as in horses and pets), the uncertainty of their presence (i.e., high losses), and location difficulties (i.e., short reading distance) will compromise the safety of camel meat (i.e., neck) for consumers, making it not fully recommendable in the camel industry.…”
Section: Previously Applied Identificationmentioning
confidence: 99%
“…Injectable half-duplex passive responders in the armpit of cattle were more suitable on the farm than smaller-sized responders or subcutaneous injection in the ear scutulum or upper lip, but they required more care and a longer time for recovery at the abattoir than for the smaller-sized devices and ear or lip injection (Conill et al ., 2000). Ghirardi et al .…”
Section: Ruminantsmentioning
confidence: 98%